Making Transport Climate Resilient : Country Report Ethiopia - World Bank (Washington, DC, 2013)
This report is the output of the World Bank-financed study on Making Trans-port Climate Resilient for Ethiopia, which is a Sub-Saharan Africa initiative to respond to the impact of climate changes on road transport.The climate scenarios The study is based on four climate scenarios selected by the World Bank to be consistent with the scenarios used in the study Economics of Adaptation to Climate Change. The scenarios span from a "global dry" future with lower temperatures and less rain than today to a "wet Ethiopia" future with more rain than today and an increase in heavy rain so that a 10- year storm in 2050 will be 25% more intensive than today. The foreseen increases in average temperatures range from -1 OC to 2 OC by 2050.